Balancing control and freedom: conditional autonomy in curriculum management in an Islamic private school in Indonesia - Khairil Azhar; Mohammad Ali; Eero Ropo; Dinn Wahyudin; Angga Hadiapurwa (Inovasi Kurikulum, 2024)
This study examines the complexities of teacher autonomy in curriculum management at a private Islamic school in Indonesia, positioned within an educational environment shaped, to a certain extent, by Indonesia's shifting educational policies—oscillating between centralization and decentralization—and various religious frameworks. Through qualitative analysis of data obtained from focused group discussions involving teachers and school management, this research reveals how teacher autonomy is both supported and constrained by institutional policies, religious values, and resource availability. The main finding of this study is the emergence of a conditional autonomy model, where teachers exercise a negotiated form of autonomy within certain boundaries. On one hand, teachers’ autonomy is influenced by national educational policies, institutional frameworks, and cultural-religious norms, indicating that this autonomy is conditional rather than absolute. On the other hand, due to practical field needs, teachers make adjustments in designing curriculum content, applying various teaching methods and strategies, and adapting teaching and assessment methods based on student conditions and time availability. These dynamics are influenced by factors such as school and foundation policies, educational supervision, resource availability, and teacher creativity. This study highlights unique challenges within the Indonesian context, where teacher autonomy in curriculum management requires a deeper, context-specific approach. A balance is needed between the demands for innovation and flexibility and the support and control mechanisms that do not restrict the space for the growth of teacher agency.   Abstrak Studi ini mengkaji kompleksitas otonomi guru dalam pengelolaan kurikulum di sebuah sekolah Islam swasta di Indonesia, yang diposisikan sebagai satu lingkungan pendidikan yang sampai taraf tertentu terbentuk oleh ragam kebijakan pendidikan di Indonesia yang bergerak seperti pendulum—sentralistik-desentralistik—serta faktor berbagai kerangka keagamaan. Melalui analisis kualitatif atas data yang diperoleh dari diskusi kelompok terpumpun (focused group discussion), yang melibatkan guru-guru dan manajemen sekolah, penelitian ini mengungkapkan bagaimana otonomi guru didukung sekaligus dibatasi oleh kebijakan institusi, nilai-nilai agama, dan ketersediaan sumber daya. Temuan utama dari studi ini adalah munculnya suatu model conditional autonomy (otonomi kondisional), di mana para guru menerapkan otonomi yang dinegosiasikan dalam batas-batas tertentu. Di satu sisi, otonomi para guru tidak terlepas dari pengaruh kebijakan pendidikan nasional, kerangka institusi, dan norma budaya-religius, yang menunjukkan bahwa otonomi tersebut bukanlah mutlak melainkan bersyarat. Namun, di sisi lain, karena kebutuhan praktikal di lapangan, para guru melakukan penyesuaian-penyesuaian dalam merancang isi kurikulum, menerapkan berbagai metode dan strategi pengajaran, serta menyesuaikan metode pengajaran dan penilaian berdasarkan kondisi siswa dan ketersediaan waktu. Dinamika ini sendiri dipengaruhi oleh berbagai faktor seperti kebijakan sekolah dan yayasan, supervisi pendidikan, ketersediaan sumber daya, dan kreativitas guru. Studi ini menunjukkan tantangan unik dalam konteks Indonesia, di mana otonomi guru dalam pengelolaan kurikulum memerlukan pendekatan yang lebih mendalam dan konteks-spesifik, di mana perlu keseimbangan antara kebutuhan akan inovasi dan fleksibilitas dengan mekanisme dukungan dan kontrol yang tidak menyempitkan ruang bagi pertumbuhan agency guru. Kata Kunci: agensi guru, kerangka keagamaan, manajemen kurikulum, otonomi guru, otonomi kondisional, otonomi kurikulum, sekolah Islam swasta